A day in September : the battle of Antietam and the world it left behind - Budiansky, Stephen (W.W. Norton & Company, 2024)
"The Battle of Antietam, which took place on September 17, 1862, remains the single bloodiest day in America's history: more than 3,600 men died in twelve hours of savage fighting, and more than 17,000 were wounded. As a turning point in the Civil War, the narrow Union victory is well-known as the key catalyst for Lincoln to issue his Emancipation Proclamation. Yet Antietam was not only a battle that dramatically changed the fortunes and meaning of the war; it also changed America in ways we feel today. No army in history wrote so many letters or kept as many diaries as the soldiers who fought in the Civil War, and Stephen Budiansky draws on this rich record to re-create the experiences of those whose lives were forever changed, whether on the battlefield or in trying to make sense of its horrors in the years and decades to follow. Antietam would usher in a new beginning in politics, military strategy, gender roles, battlefield medicine, war photography, and the values and worldview of the postwar generation."--